Analisis Perbandingan Orientasi Agregat Dan DistribusiVoid Menggunakan Agregat Baru Dan Rap YangDipadatkan Dengan Alat Marshall Hammer - Negara, Jodi Kusuma, Ir. Sri Sunarjono, M.T, Ph.D (2017)
It has been found recycle pavement using RAP (Reclaimed Asphalt Pavement) that is from unusable asphalt demolition. Good asphalt and aggregate mixture are obtaining maximum density. It can be seen from asphalt mixture asphalt mixture resulting homogeneous orientation aggregate and void distribution. This research is aim to compare orientation aggregate and void distribution using RAP and new aggregate by Marshall Hammer using cold foamed asphalt mixture. In the orientation aggregate test, the specimens are cut vertically and horizontally become two and three parts in order to acknowledge the movement of aggregate with assistance of aquarium stone to make easier the observation using coordinates point. In the void distribution test, the specimen is and cut in three parts to determine the void distributions. Based on the comparison analysis of orientation aggregate and void distribution using RAP and new aggregate by Marshall Hammer obtained void aggregate value is smaller than RAP, it means the mixture cavity is smaller and the compaction is better. In the orientation aggregate test, the stone movement at top layer move farther, it is occurred on both mixture, but the movement of new aggregate is farther than RAP means aggregate is more flexible to find out the captivity in the mixture and resulting more maximal compaction. VIM test results on RAP cut in three parts 2x75 collisions, top 11.51 %, middle 10.86 % and bottom 11.22 % and full part 12.01 %. The new aggregate mixture top 11.23 %, middle 10.70 % and bottom 10.61 % and full part 11.15 %. In the orientation aggregate RAP mixture test, the length of agen stone movement top 6.4 cm, middle 5.3 cm and bottom layer 5.8 cm. In the new aggregate top 7.0 cm, middle 5.1 cm and bottom layer 4.9 cm.